The Effect of Irrigation Water Quality, Compost Level, and Their Interaction on the Growth and Yield of Sweet Corn (Zea mays saccharata L.) Grown in Gypsum Soil - Saleh , Laith Mohammed; Kareem, Hiba Abdullah (American Journal of Biology and Natural Sciences, 2026)
In the fall of 2025, a field trial was conducted at the research station of the Department of Soil Science and Water Resources, Faculty of Agriculture, Tikrit University, to investigate the effects of irrigation water quality ( Non-saline water with a salinity of 0.467 dS/m¹ and Saline water with a salinity of 3.316 dS/m¹), plant compost application rates (0%, 1%, 2%), and their interactions on the growth and yield of sweet corn (Zea mays saccharata L.) grown in gypsum soil. The experiment used a fully randomized block design (RCBD) as a three-replicate factorial experiment. The traits investigated were plant height, panicle area, dry weight of above-ground and root parts, number of kernels per panicle, 500-grain weight, and total yield. The results showed that Non-saline water irrigation was significantly superior to Saline water irrigation in most of the traits investigated, with the highest values observed in panicle area (483.77 cm²), dry weight of vegetative organs (83.88 g plant⁻¹), dry weight of root system (32.44 g plant⁻¹), number of grains per panicle (516 grains), weight of 500 grains (154.21 g), and total yield (7410 kg ha⁻¹). Compost addition also improved all traits investigated. The 2% fertilization plot showed the highest values in average plant height (190.33 cm), panicle area (442.33 cm²), dry weight of above-ground parts (84.16 g/plant), dry weight of roots (28.83 g/plant), number of grains (533 grains), weight of 500 grains (150.92 g), and total yield (7755 kg/ha). The interaction between irrigation water quality and compost was significant for most traits. The treatment plot using Non-saline water and 2% compost yielded the best results, with a total yield of 8615 kg/ha, 579 panicles/plant, and a dry weight of 96.66 g/plant. The results indicate that compost addition improved the physical, chemical, and biological properties of gypsum soil, increasing water and nutrient absorption efficiency, thereby mitigating the adverse effects of irrigation water salinity and positively impacting plant growth and grain yield.